Effect of Education on Patient Colonoscopy Compliance: Literature Review - Sri Sulastri; Lia Natalia; Lastri Nainggolan (Indonesian Journal of Global Health Research, 2025)
Bowel preparation is essential to ensure optimal visualization during colonoscopy, thus facilitating a safe procedure and ensuring comprehensive data acquisition. An important aspect of patient preparation is education, which is critical to ensure optimal outcomes and patient compliance.The purpose of this study is to analyze the effect of education on patient compliance in performing colonoscopy examination preparation in the endoscopy unit. The research method employed was a comprehensive literature review on patient compliance with colonoscopy preparation. A comprehensive search strategy was employed, encompassing three prominent web databases: Google Scholar, Proquest, and Gale. The search was conducted from 2016 to 2024, and the full-text articles were obtained in PDF format for further analysis. The search was conducted using the keywords "colonoscopy" "education" "compliance" and "bowel preparation". The literature selection process employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses method, yielding ten relevant publications. The results of the study indicated a significant positive impact of educational interventions on patient compliance with colonoscopy preparation, as well as a concomitant enhancement in the quality of bowel preparation among individuals undergoing colonoscopy procedures. Nurse practitioners must educate patients to promote optimal outcomes from both the examination itself and the subsequent colonoscopy procedure.